A Study on suitability of II-VI semiconductor /solid Polymer thin film junctions for Photovoltaic application - Al-Bat’hia, Souad A. M.; Buys, Yose Fachmi (Elsevier Ltd., 2016)
ZnTe / polymer thin film junction has been fabricated and the photovoltaic behaviors studied. Thin films of ZnTe semiconductors were electrodeposited on indium tin oxide (ITO) conducting glass. Polymer consists of chitosan and polyethylene oxide was prepared by solution cast technique by blend and complexed with ammonium iodide (NH4I). Iodine crystals were added to the polymer–NH4I solution to provide the redox couple (I- / I3-). The ionic conductivity of the polymer electrolyte was measured and the optimized value was 1.18x10-5 S cm-1 at room temperature. The polymer film was sandwiched between the semiconductor and an ITO glass to form ITO / ZnTe / polymer electrolyte / ITO photovoltaic cells. The open circuit voltage (Voc) and short circuit current (Isc) of the fabricated cells ranges between 250-350 mV and 7.5-9.5 μA respectively.